Paganism in the Middle Ages: threat and fascination - Steel, Carlos (Mediaevalia Lovaniensia / 1, 2012)
"In this volume, the persistence, resurgence, threat, fascination, and repression of various forms of pagan culture are studied in an interdisciplinary perspective from late antiquity to the upcoming Renaissance. The contributions deal with the survival of pagan beliefs and practices as well as with the Christianization of pagan rural populations and with the different strategies of oppression of pagan beliefs. They deal with the problems raised by the encounter with pagan cultures outside the Muslim world and examine how philosophers attempted to "save" the great philosophers and poets from ancient culture notwithstanding their paganism. The contributors also study the fascination of classic "pagan" culture among friars in the fourteenth and fifteenth centuries and the imitation of pagan models of virtue and mythology in Renaissance poetry."--Book description, Amazon.com